Analisis Kurikulum Merdeka: Mampukah Merevitalisasi Bahasa Daerah? - Zaki Chandra (AGUSPATI RESEARCH INSTITUTA, 2023)
This scholarly work discusses the importance of revitalizing regional languages as an effort to protect and preserve Indonesia's cultural heritage. The discussion of regional language revitalization is crucial because it is suspected that regional languages are at risk of extinction. The extinction of regional languages has implications for Indonesia's diversity, identity, and history. In this research report, a qualitative descriptive method was employed, involving data collection through audio transcripts of oral narratives from the YouTube video